2020
DOI: 10.1002/anie.202010035
|View full text |Cite
|
Sign up to set email alerts
|

H2‐Free Re‐Based Catalytic Dehydroxylation of Aldaric Acid to Muconic and Adipic Acid Esters

Abstract: As one of the most demanded dicarboxylic acids, adipic acid can be directly produced from renewable sources. Hexoses from (hemi)cellulose are oxidized to aldaric acids and subsequently catalytically dehydroxylated. Hitherto performed homogeneously, we present the first heterogeneous catalytic process for converting an aldaric acid into muconic and adipic acid. The contribution of leached Re from the solid prereduced catalyst was also investigated with hot-filtration test and found to be inactive for dehydroxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…The product of the DODH of mucic acid is trans,trans-muconic acid, which is the most stable isomer. Mucic acid is more reactive in DODH than glucaric acid 172,174 probably because of the higher stability of the DODH product. Typical systems used a homogeneous Re catalyst and an alcohol as both a reductant and solvent.…”
Section: Glucaric Acid and Mucic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…The product of the DODH of mucic acid is trans,trans-muconic acid, which is the most stable isomer. Mucic acid is more reactive in DODH than glucaric acid 172,174 probably because of the higher stability of the DODH product. Typical systems used a homogeneous Re catalyst and an alcohol as both a reductant and solvent.…”
Section: Glucaric Acid and Mucic Acidmentioning
confidence: 99%
“…A one-pot system using the combination of a DODH catalyst (Re) + alcohol and hydrogenation catalyst + H 2 to directly obtain adipic acid from aldaric acids was also reported. 174,183,184 Bimetallic solid catalysts con-taining both Re and a noble metal for hydrogenation have been reported recently. 185,186 Considering that adipic acid is a bulk chemical, it is also better to use H 2 as a reducing agent in the DODH step.…”
Section: Glucaric Acid and Mucic Acidmentioning
confidence: 99%
“…Compared to these reductants, H 2 is a more attractive reductant for DODH in views of reductant cost, atom efficiency, suppression of side reaction of reductant‐derived products, and suppression of substrate consumption as a reductant. However, only a few systems using H 2 as a reductant were reported because the product olefins are readily hydrogenated with H 2 and the Re species might be over‐reduced to be inactive states [35–39] …”
Section: Introductionmentioning
confidence: 99%
“…However, only a few systems using H 2 as a reductant were reported because the product olefins are readily hydrogenated with H 2 and the Re species might be over-reduced to be inactive states. [35][36][37][38][39] Our group reported heterogeneous CeO 2 -supported Re catalysts using H 2 as a reductant. We first developed ReO x -Pd/ CeO 2 catalysts for hydrodeoxygenation of diols via DODH and subsequent hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…The group of adipate plasticizers is characterized by a significant improvement in the flexibility of the material at low temperatures, which is due to the linear structure of the molecule and results in a lower viscosity of adipates as compared to phthalates and other plasticizers [ 11 , 12 ]. Moreover, Hocevar et al recently reported that adipic acid can be directly produced from bio-based sources [ 13 ]. They presented the first heterogeneous catalytic process for converting an aldaric acid into muconic and adipic acid.…”
Section: Introductionmentioning
confidence: 99%